Islamic Corporate Social Responsibility, Corporate Governance in the Relationship between Profitability and Company Value - Andi Sulfati; Muslimin Kara; Amiruddin Kadir; Rika Dwi Ayu Parmitasari (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
Through the mediation of Islamic corporate social responsibility and corporate governance, this study examines the direct and indirect effects of business profitability on firm value. Using a strategy of purposive sampling, the population of this study consists of enterprises listed on the Jakarta Islamic Index-70 of the Indonesia Stock Exchange for the period 2018-2020. The AMOS 22 and Structural Equation Modeling (SEM) examined the data. The findings revealed that profitability has a beneficial impact on the value of the company. Profitability has no positive influence on corporate governance. Corporate governance has a detrimental impact on the value of a company. Profitability has no considerable beneficial effect on the value of a company. Islamic corporate social responsibility (ICSR) has a substantial positive impact on the value of a company. Profitability influences significant value as mediated by ICSR. Corporate governance cannot reconcile the profitability and company value relationship. Companies should increase their ICSR activities because it has been demonstrated that ICSR activities can become a mechanism for companies to maintain good relations and trust with all stakeholders and can be used as a new marketing tool for companies if conducted continuously, enhancing the firm's image and value. The Next Researchers can investigate the impact of additional elements affecting firm value, such as intellectual capital, media exposure, and several others.